Nickel sulfide titanium dioxide composite nanowire, preparation method and application

Nickel-containing titanium-based nanowires are obtained by nickel element ion exchange Na2Ti3O7 nanowires, and mixed with sublimated sulfur. The nickel sulfide/titanium dioxide composite nanowires are prepared through a two-step heating process. The composite positive electrode material for lithium-sulfur batteries is solved, which solves the problem of overly complex preparation methods in the prior art and achieves the effect of efficiently improving the electrochemical performance of lithium-sulfur batteries.

CN119660820AActive Publication Date: 2025-03-21CHONGQING UNIVERSITY OF SCIENCE AND TECHNOLOGY

Patent Information

Application Number
CN202411967209.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-21
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

The method used in the prior art to prepare polar transition metal composite materials with high specific surface and high activity is too complicated and it is difficult to meet the effective solution to the dissolution problem of intermediate products in lithium sulfur batteries.

Method used

Nickel-containing titanium-based nanowires were obtained by ion exchange of nickel elements, and mixed with sublimated sulfur. Nickel sulfide/titanium dioxide composite nanowires were prepared through a two-step heating process, which was used as a composite positive electrode material for lithium-sulfur batteries.

Benefits of technology

This method simplifies the preparation process of high specific surface and high activity polar transition metal composite materials, improves the adsorption and conversion ability of the lithium-sulfur battery positive electrode carrier to discharge intermediate products, thereby improving electrochemical performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119660820A_ABST
    Figure CN119660820A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of preparation of composite nanowires, in particular to a nickel sulfide titanium dioxide composite nanowire as well as a preparation method and application thereof. The preparation method comprises the following steps: taking a nickel-containing titanium-based nanowire obtained by carrying out ion exchange on a nickel element Na2Ti3O7 nanowire as a raw material; the nickel-containing titanium-based nanowire is mixed with sublimed sulfur, and then the nickel sulfide / titanium dioxide composite nanowire is prepared through a two-step heating process. The nickel sulfide / titanium dioxide composite nanowire obtained through the technical scheme is regular in morphology, and nickel sulfide and titanium dioxide are evenly distributed; adsorption of the lithium-sulfur battery positive electrode carrier to a discharge intermediate product can be effectively enhanced, conversion of the discharge intermediate product is accelerated, the electrochemical performance of the lithium-sulfur battery is improved, and meanwhile, the process for preparing the polar transition metal compound material with the high specific surface area and the high activity is simple, and production is easy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite nanowire preparation, and in particular to a nickel sulfide titanium dioxide composite nanowire, a preparation method and an application thereof. Background Art

[0002] Portable electronic devices are becoming popular in people's daily lives. The energy density of existing lithium-ion batteries has gradually reached the limit of materials, which makes it difficult to meet people's pursuit of high-energy-density energy storage materials. Lithium-sulfur batteries have the advantages of high theoretical energy density (2600Wh / Kg), abundant resources and low prices. They are considered to be the next generation of low-cost and efficient energy storage and conversion systems with great potential. However, lithium-sulfur batteries still have many problems. In particular, the intermediate products (lithium polysulfide) of lithium-sulfur battery charging and discharging are easily dissolved in the electrolyte, resulting in the loss of active substances.

[0003] In order to solve the problem of improving the dissolution of intermediate products, researchers have made a lot of attempts. Among them, the use of transition metal complexes as polar electrocatalysts has become the mainstream of current research. It has two main functions. First, transition metal complexes and lithium-sulfur battery intermediate products are both polar materials, so transition metal complexes can effectively adsorb intermediate products, thereby alleviating their dissolution into the electrolyte; second, transition metal complexes can accelerate the conversion of lithium polysulfide, thereby reducing the existence time of soluble intermediate products. Therefore, it is urgent to prepare polar transition metal complex materials with high specific surface area and high activity in a simple way. Summary of the invention

[0004] The purpose of the present invention is to provide a nickel sulfide titanium dioxide composite nanowire, a preparation method and an application thereof, so as to solve the problem that the methods for preparing high specific surface area and high activity polar transition metal composite materials in the prior art are too complicated.

[0005] To achieve the above object, the present invention provides a method for preparing nickel sulfide-titanium dioxide composite nanowires, the method for preparing nickel sulfide-titanium dioxide composite nanowires comprising the following steps: 2 g of anatase titanium dioxide powder was mixed with 80 mL of 10 mol / L sodium hydroxide solution and transferred to a high-pressure hydrothermal autoclave for constant temperature reaction to obtain Na2Ti3O7 nanowires; 1 g of the obtained Na2Ti3O7 nanowires was subjected to hydrothermal reaction with 80 mL of 0.5 mol / L nickel acetate aqueous solution in an oven to obtain nickel-containing titanium-based nanowires; 1 g of the prepared nickel-titanium-based nanowires was mixed evenly with 1 g of sublimated sulfur, and then placed in a tubular furnace in an argon atmosphere, and heated in two steps to obtain nickel sulfide / titanium dioxide composite nanowires.

[0006] Among them, in the step of "taking 2g of anatase phase titanium dioxide powder and mixing it with 80mL of 10 mol / L concentration of sodium hydroxide solution, and transferring it to a high-pressure hydrothermal autoclave for constant temperature reaction to obtain Na2Ti3O7 nanowires", the temperature of the constant temperature reaction is 200°C, and the time of the constant temperature reaction is 24h.

[0007] Wherein, in the step of "taking 1 g of the obtained Na2Ti3O7 nanowires and conducting a hydrothermal reaction with 80 mL of nickel acetate aqueous solution in an oven to obtain nickel-titanium-based nanowires", the temperature of the oven is set to 60°C, and the time of the hydrothermal reaction is 12 h.

[0008] Wherein, in the step of “taking 1 g of the prepared nickel-titanium-based nanowires and 1 g of sublimated sulfur and mixing them evenly, placing them in a tubular furnace in an argon atmosphere, and heating them in two steps to obtain nickel sulfide / titanium dioxide composite nanowires”, during the two-step heating process: The temperature range of the first step is 100°C-160°C, and the temperature is kept for 1 hour-20 hours; The temperature range of the second step is 400°C-800°C, and the temperature is kept for 10 minutes-200 minutes.

[0009] Among them, in the step of "taking 1 g of the prepared nickel-titanium-based nanowires and 1 g of sublimated sulfur and mixing them evenly, placing them in a tubular furnace with an argon atmosphere, and performing two-step heating to obtain nickel sulfide / titanium dioxide composite nanowires", the heating rate of the two-step heating is 1-10°C / minute.

[0010] The present invention also provides a nickel sulfide-titanium dioxide composite nanowire, which is prepared by the method for preparing the nickel sulfide-titanium dioxide composite nanowire as described above.

[0011] The present invention also provides a nickel sulfide titanium dioxide composite nanowire, and its application in a composite positive electrode material of a lithium sulfur battery.

[0012] Wherein, the specific preparation method of the composite positive electrode material is: Sublimated sulfur, nickel sulfide / titanium dioxide composite nanowires and carbon nanotubes in a mass ratio of 80:16:4 were uniformly mixed, and the mixture was heated to 155° C. and maintained for 12 hours to obtain a sulfur / nickel sulfide / titanium dioxide composite positive electrode material.

[0013] The present invention discloses a nickel sulfide titanium dioxide composite nanowire, a preparation method and an application thereof. The nickel-containing titanium-based nanowire obtained by exchanging Na2Ti3O7 nanowires with nickel element ions is used as a raw material. The nickel-containing titanium-based nanowire is mixed with sublimated sulfur and then subjected to a two-step heating process to obtain a nickel sulfide / titanium dioxide composite nanowire. The nickel sulfide / titanium dioxide composite nanowire obtained by the technical solution has a regular morphology, and nickel sulfide and titanium dioxide are evenly distributed, which can effectively enhance the adsorption of discharge intermediates by the positive electrode carrier of a lithium-sulfur battery and accelerate their conversion, thereby improving the electrochemical performance of the lithium-sulfur battery. At the same time, the technical solution is simple in the process of preparing a high specific surface area and high activity polar transition metal composite material, and is easy to produce. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0015] Figure 1 It is a flow chart of the steps of the method for preparing nickel sulfide titanium dioxide composite nanowires provided by the present invention.

[0016] Figure 2 This is the XRD spectrum of the nickel sulfide / titanium dioxide composite nanowire provided by the present invention.

[0017] Figure 3 This is a SEM photo of the nickel sulfide / titanium dioxide composite nanowire provided by the present invention.

[0018] Figure 4 This is the first charge and discharge curve of the nickel sulfide / titanium dioxide composite nanowire provided by the present invention for a lithium-sulfur battery at a rate of 0.2C.

[0019] Figure 5 The present invention provides a cycle stability curve of the nickel sulfide / titanium dioxide composite nanowires used in lithium-sulfur batteries at a rate of 0.2C. DETAILED DESCRIPTION

[0020] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.

[0021] See also Figures 1 to 5The present invention provides a method for preparing nickel sulfide-titanium dioxide composite nanowires, and the method for preparing nickel sulfide-titanium dioxide composite nanowires comprises the following steps: S1: 2 g of anatase titanium dioxide powder was mixed with 80 mL of 10 mol / L sodium hydroxide solution, and transferred to a high-pressure hydrothermal autoclave for constant temperature reaction to obtain Na2Ti3O7 nanowires; S2: taking 1 g of the obtained Na2Ti3O7 nanowires and reacting them with 80 mL of 0.5 mol / L nickel acetate aqueous solution in an oven for hydrothermal reaction to obtain nickel-containing titanium-based nanowires; S3: Take 1 g of the prepared nickel-titanium-based nanowires and 1 g of sublimated sulfur and mix them evenly, place them in a tubular furnace in an argon atmosphere, and heat them in two steps to obtain nickel sulfide / titanium dioxide composite nanowires.

[0022] In this embodiment, nickel-containing titanium-based nanowires obtained by exchanging Na2Ti3O7 nanowires with nickel element ions are used as raw materials. The nickel-containing titanium-based nanowires are mixed with sublimated sulfur and then prepared into nickel sulfide / titanium dioxide composite nanowires through a two-step heating process. The nickel sulfide / titanium dioxide composite nanowires obtained by the technical scheme have regular morphology, and nickel sulfide and titanium dioxide are evenly distributed, which can effectively enhance the adsorption of discharge intermediates by the positive electrode carrier of the lithium-sulfur battery and accelerate their conversion, thereby improving the electrochemical performance of the lithium-sulfur battery. At the same time, the process of preparing high specific surface area and high activity polar transition metal composite materials by the technical scheme is simple and easy to produce.

[0023] Furthermore, in step S1, the temperature of the isothermal reaction is 200° C., and the time of the isothermal reaction is 24 hours.

[0024] Furthermore, in step S2, the temperature of the oven is set to 60°C, and the time of the hydrothermal reaction is 12 hours.

[0025] Further, in step S3, during the two-step heating process: The temperature range of the first step is 100°C-160°C, and the temperature is kept for 1 hour-20 hours; The temperature range of the second step is 400°C-800°C, and the temperature is kept for 10 minutes-200 minutes.

[0026] Furthermore, the heating rate of the two-step heating is 1-10°C / min. The present invention also provides a nickel sulfide-titanium dioxide composite nanowire, which is prepared by the method for preparing the nickel sulfide-titanium dioxide composite nanowire as described above.

[0027] The present invention also provides a nickel sulfide titanium dioxide composite nanowire, and its application in a composite positive electrode material of a lithium sulfur battery.

[0028] Wherein, the specific preparation method of the composite positive electrode material is: Sublimated sulfur, nickel sulfide / titanium dioxide composite nanowires and commercial carbon nanotubes in a mass ratio of 80:16:4 were uniformly mixed, and the mixture was heated to 155° C. and maintained for 12 hours to obtain a sulfur / nickel sulfide / titanium dioxide composite positive electrode material.

[0029] Furthermore, the obtained sulfur / nickel sulfide / titanium dioxide composite positive electrode material and conductive carbon (Super P), conductive carbon (VGCF) and binder (PVDF) were dispersed in NMP solvent at a mass ratio of 7:1:1:1 to form a uniform slurry, which was then coated on aluminum foil and dried to obtain a lithium-sulfur battery positive electrode. Under the protection of an argon atmosphere, a 2035-type button cell was assembled for electrochemical performance testing, in which the negative electrode was a metal lithium sheet, and the electrolyte was 1 mol / L LiTFSI and 2 wt% LiNO3 dissolved in a DOL / DME mixed solution.

[0030] What is disclosed above is only a preferred embodiment of the present invention, and it certainly cannot be used to limit the scope of rights of the present invention. Ordinary technicians in this field can understand that all or part of the processes of the above embodiment and equivalent changes made according to the claims of the present invention still fall within the scope of the invention.

Claims

1. A method for preparing nickel sulfide-titanium dioxide composite nanowires, characterized in that: The steps include: 2 g of anatase titanium dioxide powder was mixed with 80 mL of 10 mol / L sodium hydroxide solution and transferred to a high-pressure hydrothermal autoclave for constant temperature reaction to obtain Na2Ti3O7 nanowires; 1 g of the obtained Na2Ti3O7 nanowires was subjected to hydrothermal reaction with 80 mL of 0.5 mol / L nickel acetate aqueous solution in an oven to obtain nickel-containing titanium-based nanowires; 1 g of the prepared nickel-titanium-based nanowires was mixed evenly with 1 g of sublimated sulfur, and then placed in a tubular furnace in an argon atmosphere, and heated in two steps to obtain nickel sulfide / titanium dioxide composite nanowires.

2. The method for preparing nickel sulfide-titanium dioxide composite nanowires according to claim 1, characterized in that: In the step "taking 2 g of anatase titanium dioxide powder and mixing it with 80 mL of 10 mol / L sodium hydroxide solution, and transferring it to a high-pressure hydrothermal autoclave for constant temperature reaction to obtain Na2Ti3O7 nanowires", the constant temperature reaction temperature is 200°C, and the constant temperature reaction time is 24 hours.

3. The method for preparing nickel sulfide-titanium dioxide composite nanowires according to claim 2, characterized in that: In the step "taking 1 g of the obtained Na2Ti3O7 nanowires and subjecting them to a hydrothermal reaction with 80 mL of nickel acetate aqueous solution in an oven to obtain nickel-containing titanium-based nanowires", the temperature of the oven was set to 60°C, and the hydrothermal reaction time was 12 h.

4. The method for preparing nickel sulfide-titanium dioxide composite nanowires according to claim 3, characterized in that: In the step of "taking 1 g of the prepared nickel-containing titanium-based nanowires and 1 g of sublimed sulfur and mixing them evenly, placing them in a tubular furnace in an argon atmosphere, and heating them in two steps to obtain nickel sulfide / titanium dioxide composite nanowires", during the two-step heating process: The temperature range of the first step is 100°C-160°C, and the temperature is kept for 1 hour-20 hours; The temperature range of the second step is 400°C-800°C, and the temperature is kept for 10 minutes-200 minutes.

5. The method for preparing nickel sulfide-titanium dioxide composite nanowires according to claim 4, characterized in that: In the step of "taking 1 g of the prepared nickel-titanium-based nanowires and 1 g of sublimated sulfur and mixing them evenly, placing them in a tubular furnace in an argon atmosphere, and performing two-step heating to obtain nickel sulfide / titanium dioxide composite nanowires", the heating rate of the two-step heating is 1-10°C / min.

6. A nickel sulfide-titanium dioxide composite nanowire, characterized in that: The nickel sulfide titanium dioxide composite nanowires are prepared by the preparation method of the nickel sulfide titanium dioxide composite nanowires as claimed in claim 5.

7. A nickel sulfide titanium dioxide composite nanowire as claimed in claim 6, characterized in that: Composite cathode materials used in lithium-sulfur batteries, The specific preparation method of the composite positive electrode material is: Sublimated sulfur, nickel sulfide / titanium dioxide composite nanowires and carbon nanotubes in a mass ratio of 80:16:4 were uniformly mixed, and the mixture was heated to 155° C. and maintained for 12 hours to obtain a sulfur / nickel sulfide / titanium dioxide composite positive electrode material.

Citation Information

Patent Citations

  • Nano titanium dioxide / copper sulphide nano composite material

    CN107051545A

  • S@TiO2 / polypyrrole composite material for a lithium sulfur battery cathode and preparation method thereof

    CN108832098A

  • A lithium sulfide battery cathode material and a preparation method thereof

    CN109037657A

  • Lithium-sulfur battery cathode composite material and preparation method thereof

    CN110474029A

  • Transition metal oxide-sulfur composite materials for cathodes in lithium-sulfur batteries and preparation method thereof

    KR1020160141615A

Cited By

  • Preparation method and application of Co-TiO2-coated CNTs three-dimensional composite lithium-sulfur battery positive electrode nano material

    CN121035224A